Advance in photonic crystal solar cells. (December 2019) - Liu, Wei; Ma, Hailing; Walsh, Annika
Abstract: Photonic crystals have been widely used in solar cells in recent years because of their unique optical properties such as photonic band gap and "slow photon" effect. The introduction of photonic crystals can adjust the propagation and distribution of photons in solar cells. Therefore, a full understanding of the optical properties of photonic crystals and the correct use of photonic crystals are the key to improve the photoelectric conversion efficiency. At present, photonic crystal structures are widely used in dye sensitized solar cell (DSSC) and quantum dots sensitized solar cell (QDSSC), but relatively few in the field of perovskite solar cell (PSC). In this paper, the applications of different types of photonic crystals in silicon solar cells and sensitized solar cells are summarized, and the possible problems are analyzed and commented. It is pointed out that although photonic crystals have many excellent optical control properties, it is difficult to meet the thickness requirements of PSC due to the limitations of preparation technology and structure of photonic crystals. At present, the photoelectric conversion efficiency of photonic crystal PSC is generally low. Therefore, develop new technology for preparing the large area and high quality ultra-thin photonic crystals, make a profound study of photonic crystal light control mechanism, design new structures, and explore new functions of photonic crystals will become the future development direction of photonic crystal solar cells. Highlights: The preparation methods of photonic crystal are introduced. Application of photonic crystals in silicon solar cells is discussed. Future development direction of photonic crystal solar cells is put forward.